Music in African churches - Lury, Canon E. E. (International Library of African Music, 1956)
The story goes that a very beautiful setting of the Te Deum, based on a Native African melody, was sung On a great occasion in Kampala Cathedral. One of the members of U.M.C.A., was present, and, in conversation afterwards, remarked to the Bishop of Uganda how much he admired it. Shortly afterwards, however, at luncheon a very keen and educated African Christian leaned across to the same Bishop and said "Bishop, you must never allow that Te Deum to be sung again in the Cathedral; it has too many wrong associations for us.
Keywords: Ethnomusicology; Church music; Gregorian chants; Pentatonic scales; Africa; African Music